2019
DOI: 10.1080/15230430.2019.1643210
|View full text |Cite
|
Sign up to set email alerts
|

Potential shifts in zooplankton community structure in response to changing ice regimes and hydrologic connectivity

Abstract: Changing Arctic climate may alter freshwater ecosystems as a result of warmer surface waters, longer open-water periods, reduced wintertime lake ice growth, and altered hydrologic connectivity. This study aims to characterize zooplankton community composition and size structure in the context of hydrologic connectivity and ice regimes in Arctic lakes. Between 2011 and 2016, we sampled the phytoplankton, zooplankton, and fish communities from a set of representative lakes on the Arctic Coastal Plain (ACP) of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 90 publications
2
16
0
Order By: Relevance
“…4; ranging from 0.01 to 0.12), giving confidence that the MDS plots are an accurate representation of the station relationships. Similar situations in the cutting of similarity were found in previous studies (Zhang et al 2018;Beaver et al 2019;Nandy and Mandal 2020).…”
Section: Interannual Variations In Larval Fish Assemblage Structuresupporting
confidence: 87%
“…4; ranging from 0.01 to 0.12), giving confidence that the MDS plots are an accurate representation of the station relationships. Similar situations in the cutting of similarity were found in previous studies (Zhang et al 2018;Beaver et al 2019;Nandy and Mandal 2020).…”
Section: Interannual Variations In Larval Fish Assemblage Structuresupporting
confidence: 87%
“…Research in central Europe has shown that road crossings negatively affect the richness and abundance of benthic macro-invertebrates (animals living on stream beds that are a food supply to birds and fish), including protected species (Gál et al 2020). In a study of Alaskan hydrological networks, the observations suggested an effect of hydrological connectivity on food web composition, with large-bodied zooplankton more prevalent in poorly connected lakes with low fish diversity (Beaver et al 2019). Fish are especially sensitive to transport infrastructure as barriers to migration, but also because of effects on habitat quality including temperature, suspended sediments, food supply and the timing and magnitude of water flow (Trombulak and Frissell 2000).…”
Section: Biological Impacts and Mitigation -Habitat Integritymentioning
confidence: 99%
“…Emerging research from other watersheds in Alaska highlights the role of ephemerally connected habitats in supporting shifting habitat mosaics (Brennan et al 2019) and off-channel habitats (Huntsman and Falke 2019), which ultimately result in more resilience of fish communities to land use and climate change. Fish research from ACP watersheds distinctly shows higher diversity and the presence of species with subsistence value in lakes with higher connectivity (Haynes et al 2014;Laske et al 2016;Jones et al 2017), yet shallow disconnected lakes are also shown to support very high plankton and planktivorous fish productivity (Beaver et al 2019) and even provide habitat for certain life history stages of subsistence species (Heim et al 2019). At the watershed and landscape scales, the composition of catchments with varying degrees of connectivity likely plays an important role in fish community diversity and productivity such that managing for a balance of habitat connectivity classes should be prioritized.…”
Section: Applying Connectivity Classification To Land Managementmentioning
confidence: 99%